Canine Leishmaniasis in Morocco: A Descriptive Prospective Clinical Study - Houda Idrissi; Maryam Hakkour; Luc Duchateau; Renato Zanatta; Malika Kachani; Rahma Azrib; Sylvie Daminet; Faouzi Kichou; Sabrine El Asatey; Noureddine Tazi; Hamid Sahibi; Sarah El Hamiani Khatat (Veterinary Medicine International)
Canine leishmaniasis (CanL) is a zoonotic vector-borne disease that is endemic in the Mediterranean Basin including Morocco. Dogs play a major epidemiological role in this zoonosis as reservoir hosts. This study investigated the clinical manifestations of CanL in dogs naturally infected with Leishmania infantum. A total of 96 dogs presented to the Small Animal Clinic of the Hassan II Agronomy and Veterinary Institute (IAV Hassan II) of Rabat, Morocco, and were tested by RT-PCR and/or serology. Among them, 32 (33.3%) were positive to Leishmania infantum infection. The majority of the positive dogs (93.7%) came from urban areas. Most of them were male (62.5%) and purebreds (65.6%), were aged between 3 and 7 years (71.8%), and had outside activities (guarding, hunting, livestock guarding, and service activities) (71.8%) and all of them were living exclusively outdoor or had free access to the outdoor environment. Lymphadenomegaly (81.2%), dermatological disorders (65.6%) (mostly exfoliative dermatitis), weight loss (59.3%), exercise intolerance (56.2%), anorexia (28.1%), hyporexia (15.6%), and ocular lesions (28.1%) were the most frequent clinical signs and complaints recorded. Anemia and hyperproteinemia due to hyperglobulinemia were observed in 68.7% and 72.7% of the cases, respectively. These results suggest that CanL leads to various nonspecific clinical signs as described previously, making the diagnosis challenging. Since CanL is endemic in Morocco, it should be recommended to systematically test dogs displaying clinical signs compatible with this disease and to regularly screen asymptomatic at-risk dogs. It is also crucial to educate dog owners about the zoonotic aspect of the disease and to encourage intersectorial collaboration following the “One Health” concept, in order to contribute to a more effective control/prevention of human and canine leishmaniasis.